IMPLEMENTASI KEBIJAKAN GERAKAN TUNTAS BUTA AKSARA DI KECAMATAN BANAWA TENGAH KABUPATEN DONGGALA - Saiful, Saiful (Katalogis, 2018)
This study aims to determine Implementation Completed Illiteracy Movement in District Central Banawa Donggala, through qualitative descriptive approach based on the model of implementation of Edward III in Nawawi (2009: 136-138), consisting of: Communication, Resources, Disposition and Bureaucratic Structure , The number of informants as much as 7 (seven) determined by informants who know the problems that dieliti. The data collection is done by observation, interviews, and documentation. Based on the results of research and discussion, the process of policy implementation Completed Illiteracy Movement of 4 (four) communication factor, Resources, disposition and structure of bureaucracy has been running optimally. Only factors Resources, especially financial resources are still lacking, especially in terms of funding Illiteracy Program Completed in Donggala district included in the district of Central Banawa.